2001
DOI: 10.1002/1521-4095(200108)13:16<1253::aid-adma1253>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Application of Au-Shell/Polystyrene Beads and Au-Shell/Magnetic Beads

Abstract: Multifunctional core–shell particles composed of magnetic particles covered with a gold nanoshell can be induced to align into conducting lines upon application of a magnetic field (see Figure). The formation of Au clusters and “streaky” gold nanoparticles on the surface of the PS beads is demonstrated and the preparation, characterization, and applications of magnetic and polystyrene beads featuring a gold shell are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
151
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(155 citation statements)
references
References 12 publications
(15 reference statements)
3
151
0
Order By: Relevance
“…Hollow Ag/Au shells can be fabricated by using silica [30] or polystyrene [31][32][33] spheres as templates. For our application, polystyrene (PS) is clearly the preferred choice as micro beads with a narrow size distribution are readily available.…”
Section: Templatingmentioning
confidence: 99%
“…Hollow Ag/Au shells can be fabricated by using silica [30] or polystyrene [31][32][33] spheres as templates. For our application, polystyrene (PS) is clearly the preferred choice as micro beads with a narrow size distribution are readily available.…”
Section: Templatingmentioning
confidence: 99%
“…It has been previously shown that extinction spectra of incomplete, highly fragmented nanoshells do not exhibit geometrical resonances [8], but are dominated instead by absorption resonances of the metal clusters on the spheres [9].…”
mentioning
confidence: 99%
“…Spectra of sparsely coated spheres as in Fig.2(a) exhibit only a single peak centered near 420nm. This is a signature of the excitation of the dipolar plasmon eigenmodes of individual, non-aggregated silver nanocrystals nucleated on the spheres [9]. Due to the dilute metal surfacecoverage, these modes do not couple to the weak Mie resonances of the dielectric spheres, and are therefore independent of sphere size.…”
mentioning
confidence: 99%
“…Preparation of Au/TiO 2 nanorod composites and modification of BDD electrode Au/TiO 2 nanorod composites were prepared based on the literatures. [24][25][26][27] Firstly, 1 wt%, 0.6 mL HAuCl 4 solution was added into the dispersed TiO 2 nanorods suspension (40 mL, pH 1.5) under stirring vigorously and keep stirred for several hours to allow complete adsorption of negatively charged [AuCl 4 ] -ions onto the positively charged TiO 2 nanorods surface. Reduction of [AuCl 4 ] -was achieved by the dropwise addition sodium borohydride (0.5 mg mL -1 ) until a color change was observed.…”
Section: Experimental Chemicals and Apparatusmentioning
confidence: 99%